2009
DOI: 10.1021/jp908944e
|View full text |Cite
|
Sign up to set email alerts
|

Higher Susceptibility to Halothane Modulation in Open- Than in Closed-Channel α4β2 nAChR Revealed by Molecular Dynamics Simulations

Abstract: The neuronal α4β2 nicotinic acetylcholine receptor (nAChR) is a potential molecular target for general anesthetics. It is unclear, however, whether anesthetic action produces the same effect on the open and closed channels. Computations parallel to our previous open channel study (J. Phys. Chem. B, 2009) were performed on the closed-channel α4β2 nAChR to investigate the conformationdependent anesthetic effects on channel structures and dynamics. Flexible ligand docking and over 20-ns molecular dynamics simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 64 publications
9
38
0
Order By: Relevance
“…Moreover, residues in the GABA A and glycine receptors have been identified that contribute to positive modulation of those receptors, using photolabeling and mutagenesis (1,3,(19)(20)(21)(22)(23)(24); some of these residues are thought to lie at the subunit interfaces in a site analogous to the intersubunit sites we observe, according to experimentally confirmed (34) homology models based on the nAChR. A similar site is occupied in simulations of halothane interacting with the nAChR (30,35). The site is highly suggestive as an allosteric modulation site, as the M2-M3 loop is thought to act in transduction of a ligand binding signal to the pore (12).…”
Section: Resultssupporting
confidence: 60%
“…Moreover, residues in the GABA A and glycine receptors have been identified that contribute to positive modulation of those receptors, using photolabeling and mutagenesis (1,3,(19)(20)(21)(22)(23)(24); some of these residues are thought to lie at the subunit interfaces in a site analogous to the intersubunit sites we observe, according to experimentally confirmed (34) homology models based on the nAChR. A similar site is occupied in simulations of halothane interacting with the nAChR (30,35). The site is highly suggestive as an allosteric modulation site, as the M2-M3 loop is thought to act in transduction of a ligand binding signal to the pore (12).…”
Section: Resultssupporting
confidence: 60%
“…Simulations of nicotinic receptors based on the low-resolution Torpedo structures revealed conformation-dependent binding of the volatile anesthetics halothane and isoflurane that could influence domain interactions or occlude the pore (Vemparala et al, 2006;Brannigan et al, 2010;Liu et al, 2010). More recently, the characterization of both atomicresolution structure and anesthetic sensitivity in GLIC provided valuable new simulation templates.…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…Automated docking has been used to provide initial coordinates for further unrestrained simulations[43, 85, 86], which has primarily indicated sites on the surface of the protein or at the interface between the ECD and TMD. The alternative flooding approach[87, 88] begins the simulation with a (usually high) concentration of the anesthetic dispersed randomly in the water and allows it to partition into the membrane and protein sites.…”
Section: Pharmacologymentioning
confidence: 99%
“…Although automated docking methods cannot typically be used to measure an absolute binding affinity, Bertaccini et al[90] demonstrated that automated docking scores of propofol analogs display log linear correlation with EC 50 s for GABAAr potentiation, indicating that such scores can be used to estimate relative a nities of similar compounds. Liu et al [85, 86] used AFEP to estimate absolute binding a nities of halothane for both open and closed conformations of an α 4 β 2 model of a neuronal nAChR, finding that shallow binding sites tested were low-affinity but a deeper intersubunit site indicated by experiments was moderate to high affinity. AFEP calculations of isoflurane and propofol binding to two locations in GLIC (Figure 4), the pore and the allosteric intrasubunit site indicated by crystal structures, predicted that isoflurane has higher affinity for the pore while propofol has similar affinity for the pore and intrasubunit site.…”
Section: Pharmacologymentioning
confidence: 99%